A Review on Neuropharmacology: Mechanisms, Drug Classes, and Clinical Applications - Asha D. Thakor; Rakshit M Dharajiya; Misbah Z. Shaikh; Amar M. Raval (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Neuropharmacology is a vital branch of pharmacology that focuses on the interaction of drugs with the nervous system, particularly the central and peripheral nervous systems. It plays a crucial role in understanding neurotransmission and in the treatment of neurological, psychiatric, and neurodegenerative disorders such as depression, schizophrenia, epilepsy, Parkinson’s disease, and Alzheimer’s disease. Methods:This review was conducted through a comprehensive analysis of existing experimental and clinical literature on neuropharmacology. Key areas reviewed include the organization of the nervous system, major neurotransmitters, synaptic transmission mechanisms, mechanisms of drug action, classification of neuropharmacological agents, and their clinical applications. Special emphasis was placed on drug–receptor interactions, neurotransmitter modulation, and challenges in central nervous system drug delivery, including blood–brain barrier limitations. Results: The review highlights that neuropharmacological drugs exert their effects primarily by modulating neurotransmitter release, receptor activation or blockade, reuptake inhibition, and enzyme inhibition. Major drug classes such as antidepressants, antipsychotics, anxiolytics, antiepileptics, analgesics, and antiparkinsonian agents have shown significant clinical benefits. However, adverse effects, drug dependence, tolerance, and limited brain penetration remain major concerns. Emerging strategies such as nanocarriers, receptor-mediated transport, and intranasal delivery show promise in overcoming current therapeutic limitation